2020
DOI: 10.1002/bse.2609
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perception of reverse logistics practices on supply chain performance

Abstract: Managing supply chain performance is essential for value generation to stakeholders. Nonetheless, this process has become overly complicated due to environmental concerns that lead to policy changes, customer preferences, and business activities. Reverse logistics is an environmentally friendly practice that can be critical in improving the environmental performance of construction operations. This paper examines the perceived role of reverse logistics practices on supply chain performance criteria—for example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 56 publications
(61 reference statements)
1
46
0
Order By: Relevance
“…According to Pushpamali et al (2021), RL is perceived as an environmentally friendly practice in construction operations. In this study, in fact, it is highlighted that its implementation leads to a significant reduction of cost for materials in comparison with a purchase of new ones.…”
Section: Resultsmentioning
confidence: 99%
“…According to Pushpamali et al (2021), RL is perceived as an environmentally friendly practice in construction operations. In this study, in fact, it is highlighted that its implementation leads to a significant reduction of cost for materials in comparison with a purchase of new ones.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, regulatory authorities require information on waste quantities from demolition contractors, waste processors, and landfills for record keeping and policy development purposes. Both waste processors and suppliers should disseminate information regarding reprocessed products to the market, to secure market demand (Pushpamali et al, 2021). Finally, landfills need to communicate with waste processors on the availability of landfill facilities, landfilling charges, and the availability of recoverable material for reprocessing.…”
Section: Organization Of Dw Rlsc Processes Based On Material Informat...mentioning
confidence: 99%
“…A gap in information exchange between secondary material users and upstream waste processors was also revealed through literature. Secondary material users complained that information available on reprocessed materials, such as quality, quantity, and source, are limited when compared to that of virgin materials (Pushpamali et al, 2021). This is further substantiated by Oyedele et al (2014), where the authors identified that waste processors do not communicate well with material users, and little has been done to improve market knowledge on reprocessed materials.…”
Section: Inhibitors Of External Integration Across Dw Rlscsmentioning
confidence: 99%
“…Reverse logistics (RL) is one of the most creative activities that have helped manufacturers boost their market efficiency while protecting the environment and the global community at large. Over the years, manufacturers have implemented various environmental management approaches in an effort to ensure efficient utilization of resources, waste reduction, and meeting the social expectations of the environment (Wong, Lai, Shang, Lu, & Leung, 2012), while reducing sourcing costs (Pushpamali, Agdas, Rose, & Yigitcanlar, 2020). The early 1990s saw RL emerging as a solution to organizations' quests to maximize economic benefits while meeting governmental regulations (Temucin & Tuzkaya, 2020).…”
Section: Introductionmentioning
confidence: 99%